Identifikasi Parameter Model First Order Plus Dead Time (FOPDT) untuk Analisis Dinamika Proses pada Reboiler 212-V14 Unit Hydrocracker Kilang Minyak - Adzra Afrina Pradata; Herry Purnama (Dewantara Journal of Technology, 2026)
This study aims to analyze the effect of changes in TOP V14 temperature and light key (LK) flow rate on the dynamic behavior of a fractionation column process, as well as to develop a mathematical model for designing an Advanced Process Control (APC) algorithm. The research employed an experimental approach combined with system identification to determine the process response characteristics. The results show that increasing the TOP temperature from 112°C to 128°C raises the LK flow rate from 11 to 14 flow units, with a process gain (Kp) of 0.517 and a time constant (τ) of 4.989 minutes. At the same time, the heavy key (HK) flow rate also increases from 22 to 35 flow units, with a Kp value of 0.998 and a τ value of 3.777 minutes. Although the HK response reaches its final condition relatively quickly, the presence of dead time still causes a delay in the overall process response. These findings indicate that the implementation of APC for controlling LK and HK has strong potential to enhance process performance and provide significant economic benefits.